2018
DOI: 10.1038/s41598-018-30196-0
|View full text |Cite
|
Sign up to set email alerts
|

Citrobacter freundii fitness during bloodstream infection

Abstract: Sepsis resulting from microbial colonization of the bloodstream is a serious health concern associated with high mortality rates. The objective of this study was to define the physiologic requirements of Citrobacter freundii in the bloodstream as a model for bacteremia caused by opportunistic Gram-negative pathogens. A genetic screen in a murine host identified 177 genes that contributed significantly to fitness, the majority of which were broadly classified as having metabolic or cellular maintenance function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 83 publications
5
72
0
1
Order By: Relevance
“…It is found in soil, water, food and as a commensal in the gastrointestinal tract of humans and other animals [56,57,59]. However, it is increasingly a nosocomial and environmental pathogen, causing pneumonia, diarrhea, urinary tract and bloodstream infections [59][60][61][62][63][64][65][66]. Food poisoning cases caused by C. freundii isolates have been reported [59,62].…”
Section: Introductionmentioning
confidence: 99%
“…It is found in soil, water, food and as a commensal in the gastrointestinal tract of humans and other animals [56,57,59]. However, it is increasingly a nosocomial and environmental pathogen, causing pneumonia, diarrhea, urinary tract and bloodstream infections [59][60][61][62][63][64][65][66]. Food poisoning cases caused by C. freundii isolates have been reported [59,62].…”
Section: Introductionmentioning
confidence: 99%
“…In Y. pseudotuberculosis, several Tat substrates are identified critical to cause systematic infection, among which ΔsufI shows the largest attenuation [35]. In Citrobacter freundii, it has also been shown that sufI mutation results in a very significant in vivo fitness defect [15]. A recent study in S. Typhimurium demonstrates that the deletion of the two Tat-dependent amidase encoding genes leads to significant in vivo fitness attenuation, mainly due to cell division defect especially in the inflamed gut where stress conditions including high osmolarity and antimicrobial peptides are present [18].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diversity of Tat substrate proteins, Tat system disruption causes pleiotropic defects, affecting bacterial growth, cell division, motility, biofilm formation, iron acquisition, stress response, etc [9,10]. Moreover, the crucial role of the Tat system in pathogenesis has been reported in several important bacterial pathogens, including Pseudomonas aeruginosa [11], E. coli O157 [12], Salmonella enterica serovar Typhimurium [13,14], Citrobacter freundii [15], and Yersinia pseudotuberculosis [16]. Efforts have been made by several research groups to unravel how the Tat system affects bacterial virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Citrobacter freundii (C. freundii) is a gram-negative bacterium, motile, oxidase negative and non-capsulated (Lakhundi et al, 2017;Liu et al, 2018). Citrobacter freundii is one of the most important gram-negative bacteria cause urinary tract infection and other diseases in human such as bacteremia (Park et al, 2013;Ouyang et al, 2018;Anderson et al, 2018). Recently, Citrobacter freundii isolated from hospitals patients with urinary tract infection becomes more resistant to different antibiotics like beta-lactamase, 3rd generation cephalosporins and aminoglycosides (Aljanaby and Gafil 2013; Castanheira et al, 2018;Akinbami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%